Allergic Rhinitis Control Test questionnaire‐driven stepwise strategy to improve allergic rhinitis control: a prospective study. Issue 11 (20th July 2016) - Wang, Y.; Chen, H.; Zhu, R.; Liu, G.; Huang, N.; Li, W.; Yang, L.; Zhang, S.; Qi, S.; Daurès, J.‐P.; Chiriac, A. M.; Demoly, P.
Abstract: Background: Allergic Rhinitis Control Test (ARCT) has been validated for assessing allergic rhinitis (AR) control and identifying severe AR. The aim of the study was to assess the ARCT questionnaire as a tool for stepwise pharmacotherapy. Methods: A standard pharmacotherapy regimen from Step 1 (oral second‐generation H1 antihistamine as needed) to Step 5 (oral corticosteroid) was carried out prospectively in a Chinese AR population. The AR patients were initiated with Allergic Rhinitis and its Impact on Asthma (ARIA) appropriate step treatment and assessed with ARCT every 15 days. If ARCT score was equal or above 20 (controlled AR) and maintained for 15 days, the patient would finish the study; if ARCT score was strictly <20 (uncontrolled AR), the patient would receive higher step treatment according to a predefined open design up to Step 5. The different AR control subgroups were compared. Results: A total of 255 patients were enrolled in the study; 5 patients dropped out and 2 (0.8%) were controlled at day 0, 85 (34.0%) at day 15, 177 (70.8%) at day 30, 222 (88.8%) at day 45, 241 (96.4%) at day 60 and 242 (96.8%) at day 75. Only 8 (3.2%) patients remained uncontrolled at the endpoint of the study. Patients with ARIA moderate/severe or persistent symptoms, moderate/severe impaired quality of life, asthma history, rhinorrhea and cough symptoms always needed up to Step 4 (nasal corticosteroid plus antihistamine) and prolonged treatments to achieve disease control. Conclusions: The majority of AR can be controlled with standard stepwise treatment. ARCT offers an objective criterion for the stepwise pharmacotherapy of AR.